PELAKSANAAN PROGRAM KARASO KANTIKA RO KATAHO (3K) DALAM MENGEDUKASI KARAKTER PEDULI LINGKUNGAN ANAK DI TKN PEMBINA SOROMANDI - Karlina, Lilis; Ramadhan, Syahru; Hermansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the importance of instilling an environmentally conscious character from an early age through a local cultural approach relevant to children’s lives. At TKN Pembina Soromandi, the values of Bima’s traditional wisdom such as Karaso, Kantika, and Kataho (3K) serve as the foundation for shaping children’s environmentally conscious behavior. Before this program was implemented systematically, there was still a low level of awareness among children regarding personal hygiene and the environment, as well as a lack of practice in mutual cooperation at school. Therefore, this study aims to provide an in-depth description of the implementation of the Karaso Kantika ro Kataho (3K) program as an educational effort to foster an environmentally conscious character in children at TKN Pembina Soromandi. The research design employed was qualitative research with a descriptive approach. The data sources for this study consisted of teachers, the school principal, and students at TKN Pembina Soromandi. Data collection methods included direct observation of learning activities, in-depth interviews with teachers and the school principal, and documentation of 3K activities. The data were analyzed using Miles and Huberman’s interactive analysis model through the stages of data reduction, data presentation, and drawing conclusions. The research results indicate that the implementation of the 3K program encompasses several key activities: fostering personal hygiene (Karaso), collaborative efforts to maintain the school environment’s cleanliness (Kantika), planting and caring for plants (Kataho), and reflecting on values through thematic songs and stories. Through these activities, children demonstrated increased awareness of maintaining cleanliness, a love for natural beauty, and a sense of social responsibility toward the environment. Thus, the Karaso Kantika ro Kataho (3K) program is effective in internalizing environmental values rooted in local wisdom.